Filosofi Gunungan dalam Pagelaran Wayang Kulit Ditinjau dari Perspektif Islam - Andani, Sahrul (Lembaga Yasin AlSys, 2023)
This study examines the Gunungn philosophy in the implementation of wayang kuliuit in terms of an Islamic perspective. This type of research is qualitative research which describes data using a series of sentences. The method used in this research is descriptive method. The results of this study show that in Islam, the sentence of shahadah is the key to Heaven towards the salvation of the world and the hereafter. A Muslim must adhere to the principles of Islamic teachings to be successful in life. In wayang, new Islamic values are built, not changing standard stories. Walisongo created a new character in the Mahabarata and Ramayana stories with an Islamic social vision through the behavior of the punakawan. Wayang kulit introduces Islam through wayang displays with religious values inserted after adopting the Mahabharata and Ramayan books from India. To follow the story, the audience must recognize the important characters. Wayang kulit is different from other wayang puppets and is popular in Indonesia because it is considered a rich cultural heritage that continues to grow.